Phase diagram and stability of mixed-cation lead iodide perovskites: A theory and experiment combined study - Xu, Zhengwei; Zhao, Yicheng; Zhang, Jiyun; Chen, Keqiu; Brabec, Christoph; Feng, Yexin (Physical Review Materials, 2020)
Alloying structurally similar perovskites to form mixed-cation lead iodide perovskites, e.g., Cs(x)FA((1-x))PbI(3), MA(x)FA((1-x))PbI(3), and Cs(x)MA(y)FA((1-x-y)) PbI3, could improve the performance of perovskite-based solar cells and light-emitting diodes. However, a phase diagram of them and a clear understanding of the underlying atomic-scale mechanism are still lacking. Using ab initio calculations combined with high-throughput experimentation, we demonstrate the phase diagram of mixed-cation lead iodide perovskites. Only a small proportion of monovalent cations (Cs+/Rb+/MA(+)) could be incorporated into the FAPbI(3)/MAPbI(3) matrix; otherwise it will be separated into delta-CsPbI3, delta-RbPbI3, MAI, etc. The smaller the radius of doping cations, the harder it is to incorporate them into a perovskite lattice and the easier it is to stabilize the perovskite phase. In FAPbI(3)-based multication perovskites, moreover, over 10 mol % alloying is needed to convert delta phase to alpha phase at room temperature. The combined upper and lower limits for doping concentration restrict the appropriate alloying ratio to a narrow window. We further plot the relative energy diagram for triple-cation perovskite Cs(x)MA(y)FA((1-x-y))PbI(3), which reveals the ideal doping ratio for uniform stable alloying. This theory-experiment-combined study provides a clear microscopic picture of phase stability and segregation for mixed-cation perovskite solids.
CRIS-Team WoS Importer:2020-10-09